Percutaneous retrieval of umbilical vein catheter fragment in an infant two months after embolization - Akın, Alper; Bilici, Meki; Demir, Fikri; Yılmazer, Murat Muhtar; İpek, Mehmet Şah; Kara, Hülya (The Turkish Journal of Pediatrics, 2018)
Umbilical vein catheterization is frequently preferred and a safe route of venous access especially in newborns. However, some cases with breaking and embolization of those catheters have been rarely reported. Herein we present a two-and-a-half-month-old infant being catheterized within first postnatal week and diagnosed to have embolization of the catheter fragment to conjunction of hepatic vein and right atrium. Percutaneous withdrawal of broken catheter was achieved despite several months after the embolization took place. We suggest that transcatheter removal of catheter fragment embolizations may be safe even in late diagnosis cases.
Keywords: breaking of catheter; percutaneous retrieval; umbilical vein catheter